If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -1x = 0.33 * 15 + 6 Multiply 0.33 * 15 17 + -1x = 4.95 + 6 Combine like terms: 4.95 + 6 = 10.95 17 + -1x = 10.95 Solving 17 + -1x = 10.95 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 10.95 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 10.95 + -17 -1x = 10.95 + -17 Combine like terms: 10.95 + -17 = -6.05 -1x = -6.05 Divide each side by '-1'. x = 6.05 Simplifying x = 6.05
| 6x-3x+y+8y-x= | | (2x-3)(x+2)=6 | | 6*n+10=83.2 | | 4x+2-x=-19 | | 2z-1.2=1.4 | | 3(4x-1)+x=5x-4+8x | | 10+0.10m=0.35 | | k^2-77=-4k | | X-4=4(x+2) | | 6x+24+2x+6=180 | | 16/y=2/3 | | 4(x+2)=5-x | | 3/5x8= | | 3x=-3+12 | | 38=3x+12+32 | | 3x+10-2x+4=26-5x | | (x^1/4)-(x^1/2)-2=0 | | 365+y=2y-3 | | 3x+2=2(5z+8)-12 | | -37-7r=-3(5r-9) | | 12x/3(x-1) | | 92-y=214 | | 56=4(3n-1) | | -11*-11*-11= | | 3c^2+12c=-15c | | -2(2x+7)-7(-8x-6)=-76 | | -4(3t-4)+6t=2t-3 | | 12=23-n | | (w+4)(2w+4)=2w^2+12 | | 2x+50+2x+30=180 | | -36=-9(x+8) | | 2(x-3)=3y-1 |